Investigating the Factors Affecting Speeding Violations in Jordan Using Phone Camera, Radar, and Machine Learning - Al-Mistarehi, Bara’ W.; Alomari, Ahmad H.; Imam, Rana; Alnaasan, Tasneem K. (Frontiers in Built Environment, 2022)
Traffic accidents are considered the leading cause of death for the age group (5-29). They cause approximately 1.3 million deaths every year. Different factors cause traffic accidents; one of them is speeding violations. This work studied speeding violations and the factors that affect them for Irbid city in Jordan. Several factors related to the driver, environment, vehicle, road, and weather conditions were studied. The analysis results showed that age, vehicle type, speed limit, the day of the week, season, accident year, accident time, license category, and light conditions affect speeding violations. Seven hot spots of speeding violations in Irbid were specified, and the free flow speed was measured using radar and video recording at these hot spots. The 85th percentile speed was estimated and the results for all locations were less than the speed limit. In addition, the radar and video measurements were compared to specify the most accurate method. The results did not show any difference between the two measurement techniques.